For a perspective curriculum: a Nietzschian provoking - Tedeschi, Sirley Lizott (2020)
This article is the result of bibliographic research and aims to analyze and discuss Nietzsche's perspectivist philosophy in order to show the implications for the field of education and curriculum. Based on the writings of Nietzsche and authors who have a dialogue with the Nietzschian work, we propose to show, at first, that the German philosopher goes beyond the assumptions of modernity and inaugurates a new dimension of philosophy by establishing perspectivism as a method of thought. In a second moment, we show how Nietzschean perspectivism potentiates ways of thinking about education and curriculum that excel, no longer for unity and identity - metaphysical categories -, but for multiplicity and difference, since it does not resort to essentialisms and universalisms.